Non-covalently coated biopolymeric nanoparticles for improved tamoxifen delivery - Chevalier, Merari Tumin (2017)
About one-fifth of cancer patients suffer from breast cancer worldwide. Polymeric nanoparticles play an important role in delivering chemotherapeutic agents in a controlled manner. Polylysine coated tamoxifen loaded poly(lactic-co-glycolic acid) nanoparticles were prepared using a single emulsion technique with subsequent non-covalently surface functionalization in order to improve nanoparticle-cell interaction and hence tamoxifen therapeutic effect. The obtained nanoparticles were fully characterized in terms of their physico-chemical properties as well of their in vitro performance against human breast adenocarcinoma cells. The successful incorporation of tamoxifen within the hydrophobic matrix of nanoparticles is evidenced by a high loading efficiency (86%). Furthermore, ideal size, morphology and hydrodynamic properties are observed being the proposed nanocarrier capable of display a valuable antiproliferative in vitro effect.